Determination Of The Planting Season Based On Wariga Local Wisdom And The Influence Of Weather Using The Simple Additive Weighting Method - I Made Pradipta; I Gede Aris Gunadi; I Nyoman Sukajaya (INFOKUM, 2022)
This study aims to implement a decision support system method in determining the planting season based on the calculation of padewasan wariga based on weather conditions. Determining the right planting season is one of the keys to the success and production of food crops. The SAW method is used in the process of calculating and determining the weights for each criterion for wariga planting and forecasting weather conditions to produce the best padewasan ranking for the next year as a reference for determining the planting season. The data collection was obtained through several stages, namely: (1) the acquisition of resident data was obtained using the interview method with an expert or wariga expert, (2) the acquisition of weather data was obtained using the observation method at the Meteorology, Climatology and Geophysics Agency of Denpasar Region III. The data obtained from the weather data acquisition stage is calculated using the moving average method to determine the weather conditions that will occur. The results showed that the implementation of a decision support system using SAW resulted in a padewasan ranking in determining the planting season in 2021. The level of accuracy of the validation effectiveness of the ranking results was measured using the Mean Avarage Precision (MAP) method. Based on the results of the calculation of the accuracy level of effectiveness using the MAP method, it can be concluded that the application of a decision support system for determining the planting season of local wisdom in Padewasan Wariga based on the current weather using the SAW method produces an accuracy percentage of 60%, so it can be categorized as feasible to be applied as a reference for determining the planting season.